COMPARATIVE BETWEEN DEMOGRAPHIC CHARACTERISTICS WITH CARING BEHAVIOR OF NURSES IN NURSING PRACTICE IN DR KUMPULAN PANE HOSPITAL TEBING TINGGI OF NORTH SUMATERA 2019 - Mestiana Br Karo Pranata; Rotua Elvina Pakpahan; Rotua Uli Pardosi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Demographic characteristics consist of age, sex, religion, length of employment, tribe, place of work and level of education. Caring behavior is a form of basic nursing practice that looked with patience, honesty, confidence, presence, touch, affection in implementing nursing actions. The study aims to analyze the comparative between demographic characteristics with caring behavior of nurses in nursing practice in Kumpulan Pane hospitals Tebing Tinggi of North Sumatera 2019. This research type a descriptive comparative with cross sectional approach. Sampling by using stratified random sampling with 75 respondents. The results showed caring behavior nurses consists of either category 25 (32.9%) and a very good 50 (67.1%). Data analysis using Manalysis with One way ANOVA. Demographic characteristics by age and caring behaviors of nurses is p-value 0.965 (p>0.05), practice areas namely p-value 0.066 (p>0.05), religion is p-value 0.135 (p>0.05), tribe is p-value 0.186 (p>0.05), length of work 0.366 p-value (p>0.05). Independent analysis of the comparative test sample demographic characteristics by gender with the nurse caring behaviors, namely p-value 0.312 (p>0.05), education namely p-value 0.336 (p>0.05). Efforts to improve or special coaching ability nurse caring behaviors by providing seminars to nurse twice a year and given a reward in the form of appreciation to those who run the caring in nursing actions